Cardiac Energy Harvesting: Multifunctional Pacemaker Lead for Cardiac Energy Harvesting and Pressure Sensing (Adv. Healthcare Mater. 11/2020). Issue 11 (10th June 2020) - Dong, Lin; Closson, Andrew B.; Jin, Congran; Nie, Yuan; Cabe, Andrew; Escobedo, Danny; Huang, Shicheng; Trase, Ian; Xu, Zhe; Chen, Zi; Feldman, Marc D.; Zhang, John X. J.
Abstract : Self‐sustainable energy generation represents a new frontier of power solution for implantable biomedical devices (IMDs). In article number 2000053 by Zi Chen, Marc D. Feldman, John X. J. Zhang, and co‐workers, an integrated cardiac energy harvesting and pressure sensing strategy is developed by using the porous P(VDF‐TrFE) films with a self‐assembly helical structure. It provides a multifunctional, transformative while practical power and diagnosis solution for cardiac pacemakers and the next generation of IMDs.